Exploring the effect of magnesium content on the electrochemical performance of aluminum anodes in alkaline batteries. (1st September 2020) - Gao, Jianxin; Fan, Hefei; Wang, Erdong; Song, Yujiang; Sun, Gongquan
Abstract: Mg is an important alloying element for Al anode in alkaline batteries. In this work, series of Al–Mg alloys have been investigated as anode materials, focusing on optimizing the Mg addition amount in Al anode with the intention of enhancing its discharge performance. The results show that solid-solute Mg improves the discharge potential of Al anode at low current density and inhibits its self-corrosion. However, excess Mg additions accelerate the self-corrosion of Al anode due to the formation of AlMg intermetallic in Al matrix. To reduce the corrosion rate and improve the discharge activity, Mg content in Al anode is optimized to be 0.5% with cooperation of electrolyte additive Na2 SnO3 . Highlights: Effect of different Mg content on discharge performance of Al anode was investigated. Mg addition in Al anode was optimized to be 0.5% at operating temperature of 50 °C. Al-0.5 Mg exhibited coulombic efficiency of 96% at 100 mA cm −2, that of 5N Al was 83%.